The Effect of Implementing Baby Gym on Gross Motor Development in Babies Aged 3-4 Months - Susmita Susmita; Ayu Devita Citra Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
Data shows that motor development disorders are experienced by 5-10% of children in the world. Disrupted motor development can be an indirect cause of increased morbidity, poverty and in the long term can hamper the country's development. One effort to prevent gross motor delays in children is by stimulating them from infancy, for example by doing baby gym exercises. The aim of this research was to determine the effect of a baby gym on gross motor development in babies aged 3-4 months. The research design uses a quasi-experimental with control group design. The intervention group is the group that carries out the baby gym. Meanwhile, the control group did not do the baby gym. Data analysis used the Mann Whitney test. The population in this study were all babies aged 3-4 months at PMB Andina Palembang. The sampling technique used a total sampling of 24 respondents who were divided into 12 intervention group respondents and 12 control group respondents. The research results showed that the average gross motor development in the intervention group after baby gym training for 2 weeks showed faster gross motor development compared to babies in the control group who were not given intervention. Meanwhile, the p value obtained was 0.001, meaning that there was a difference in gross motor development in babies who were stimulated with baby gym exercises and babies in the control group who were not given any intervention. It is recommended for health workers to intensify education about stimulating gross motor development in babies, one of which is by doing a baby gym.